Highly deficient alcohol health warning labels in a high‐income country with a voluntary system. (15th May 2018) - Tinawi, Georges; Gray, Tessa; Knight, Thomas; Glass, Chayce; Domanski, Nina; Wilson, Nick; Hoek, Janet; Thomson, George
Abstract: Introduction and Aims: To examine the prevalence and design elements of the voluntary health warning labels and related industry initiatives on a purposive sample of alcoholic beverage containers sold in New Zealand (NZ), a country with no mandatory health warning labels. Design and Methods: We selected a purposive (e.g. low‐cost) sample of 59 local and imported beers, wines and ready‐to‐drink alcoholic beverage containers available in NZ in 2016–2017. We documented the occurrence, content, size, appearance and position of messages concerning drinking during pregnancy, drink‐driving, other health effects and industry‐led initiatives that could relate to warnings; and collected data about alcohol content, standard drinks, ingredients and energy information. Results: A majority (80%) of the alcoholic beverage containers had a pregnancy‐related warning, 73% had industry‐led initiatives (e.g. advising 'responsible' consumption) and 19% had drink‐driving/heavy machinery warnings. Warning labels were small, with the average area of pregnancy‐related and drink‐driving/heavy machinery pictograms being 45 and 36 mm 2, respectively (i.e. pea‐size). The average heights of pregnancy‐related and drink‐driving text were 1.6 and 2.2 mm, respectively. Pregnancy‐related pictograms occupied between an average of 0.13% (wine) and 0.21% (ready‐to‐drink) of the available surface area of the alcoholic beverage container (i.e. less than 1/400th of the available space). Drink‐driving pictograms occupied an average of 0.12% (imported beer), and 0.13% (NZ beer) of the available surface area. Discussion and Conclusions: Voluntary recommendations in NZ appear to have been inadequate for producing health warnings on alcoholic beverage containers that are consistent with evidence‐informed recommendations for effective labels. This finding suggests that mandatory standardised labelling outlining alcohol‐related risks may be required to ensure adequate consumer information.